ЯССАВИЙ ҲИКМАТЛАРИДА МАЖОЗ ВА ҲАҚИҚАТ - Атаниязова, М.А. (SCIENCE and SOCIETY, 2022)
The article discusses the metaphor and truth, the unity of form and theme, the use of poetic means in the wisdom of Ahmad Yassavi.
Keywords: Yasawi and Sufism; wisdom and love; art of wisdom and measure; themes of enlightenment and perfection in wisdom